Impacts of COVID-19 on childhood malnutrition and nutrition-related mortality - Headey, Derek D.; Heidkamp, Rebecca A.; Osendarp, Saskia J. M.; Ruel, Marie T.; Scott, Nick; Black, Robert; Bouis, Howarth E. (Elsevier, 2020)
The unprecedented global social and economic crisis triggered by the COVID-19 pandemic poses grave risks to the nutritional status and survival of young children in low-income and middle-income countries (LMICs). Of particular concern is an expected increase in child malnutrition, including wasting, due to steep declines in household incomes, changes in the availability and affordability of nutritious foods, and interruptions to health, nutrition, and social protection services. One in ten deaths among children younger than 5 years in LMICs is attributable to severe wasting because wasted children are at increased risk of mortality from infectious diseases. Before the COVID-19 pandemic, an estimated 47 million children younger than 5 years were moderately or severely wasted, most living in sub-Saharan Africa and south Asia.